MAKNA LIRIK LAGU “TUHAN ALLAH BESERTA ENGKAU” DALAM BENTUK KAJIAN SEMANTIK - Alfa Setya Atmaja; Epifani Omega (JURNAL PENABIBLOS, 2024)
The author chose to conduct research on the song "God is with You." First, the song "God, God is with You" has a theological meaning for the life of the writer, especially when seen from the meaning of the lyrics which have broad meaning for the listeners, especially Christians. The lyrics of the song "God, God is with You" convey a message about God's presence, a call for faith, consolation,providing protection and strength to humanity. Qualitative methods with a descriptive approach were used to conduct research. The meaning of the lyrics of the song Lord Allah is with You which contains a theological message and how this message is communicated through the use of words, lyric structure and connotative meaning. These findings show that the lyrics of this song convey a message about God's inclusion, a call full of confidence and comfort that God is always present, provides protection and strength to His people in every journey of life. Through carefully chosen words, an orderly lyric structure, and impressive connotative meaning, these lyrics succeed in inviting listeners to always hold on firmly to God in joy and sorrow, with the belief that His love will never leave humanity.